Correction: Controlling dark catalysis with quasi half-cycle terahertz pulses. Issue 2 (9th January 2019) - Sá, Jacinto; Fernandes, Daniel L. A.; Pavliuk, Mariia V.; Szlachetko, Jakub
Abstract : Correction for 'Controlling dark catalysis with quasi half-cycle terahertz pulses' by Jacinto Sá et al., Catal. Sci. Technol., 2017, 7, 1050–1054.